Modul Pembelajaran Internet Of Things (Iot) Berbasis Obe Sebagai Modul Pembelajaran Revolusioner Taruna Teknik Listrik Bandara Politeknik Penerbangan Surabaya - Kabul Yunior, Yudhis Thiro; Subagyo, Edwardo (Jurnal Penelitian, 2025)
Internet of Things (IoT) is a primary need that has been widely used in various fields, including health, education, energy, transportation, housing, agriculture, livestock and the general environment. The development of industry and technology in the field of education continues to change. The world of education is currently faced with an era of digital disruption, or in the industry known as "Industry 4.0" and "society 5.0". The terms industry 4.0 and Society 5.0 refer to a new phase in the industrial revolution and changes in digital society that are highly focused on interconnectivity, automation, machine learning, artificial intelligence and real-time data. The creation of an IoT module based on Outcome Base Education (OBE) aims to provide training or workshops to learn, understand and practice the Internet of Things (IoT) platform by integrating the concept of Outcone Base Education (OBE) to students as a form of directed, measurable and integrated learning in the implementation of the learning revolution in the era of the industrial revolution 4.0 and society 5.0 The implementation of this learning module is expected to be a pioneer in the implementation of accountable, directed and integrated education in accordance with the development of industrial revolution 4.0 technology, this is because the Surabaya Aviation Polytechnic is a university under the Ministry of Transportation which implements the Tri Dharma of Higher Education with the outcome of producing the best and digitally-minded personnel in the aviation industry.